Pengembangan Aplikasi Penghitung Luas Segitiga Dengan Java - Rizka Aprilia; Robiyatul Adawiyyah; Fauzan Azhari; Muhammad Ilham Satiyar; Aditya Rizki Ramadhan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This research is research into the development of a triangle area calculator application using Java which aims to collect programming group assignments. This testing was carried out using an application built with the Java programming language and the NetBeans IDE development tool, Java programming is an important skill in the field of information technology. Therefore, build a simple application to calculate the area of ​​a triangle using the Java programming language. This research is to introduce the basic concept of how to develop a triangle area calculator application using Java in the Java programming language to make it easier for students or beginners who aim to solve this problem for beginners, to teach the steps in creating Java applications, and to provide practical experience in implementing programming concepts in real project. Data was collected using techniques for creating flowcharts into Java code, testing, debugging, and evaluating results, this application meets the criteria for good software quality.